Integrasi Pedagogi Reflektif dan Eco-Pedagogy dalam Konstruksi Kausalitas Sejarah: Membangun Kesadaran Nilai Lingkungan melalui Landscape Budaya dalam Pembelajaran Sejarah - Sudarto, Sudarto; Warto, Warto; Sariyatun, Sariyatun; Musadad, Akhmad Arif (Universitas Galuh, 2025)
The study examines the integration of reflective pedagogy and eco-pedagogy in the construction of historical causality, with a focus on building environmental awareness and values through an understanding of cultural landscapes in history education. The phenomenon of environmental unconsciousness in history education has become a primary urgency for the development of an educational model that combines critical reflection and ecological values. This approach aims to cultivate critical attitudes and ecological awareness among students by leveraging relevant historical and local cultural contexts. The study employs a descriptive qualitative method with data collection techniques including literature review, observation, and interviews. The results of the study show that the integration of these pedagogies is effective in deepening understanding of historical causality while instilling ecological values and preserving local culture as a medium for meaningful learning. The implications of this study encourage innovation in history learning that not only teaches historical causality but also builds critical ecological awareness and cultural values. These findings contribute to the development of new models of history learning that are environmentally and culturally aware.